2014
DOI: 10.4238/2014.may.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 promotes nonamyloidgenic cleavage of amyloid precursor protein via a cholesterol-dependent pathway

Abstract: ABSTRACT. Ginsenoside Rh2 (Rh2) is a ginseng derivative used in Chinese traditional medicine. We investigated whether Rh2 can help prevent Alzheimer's disease symptoms and examined underlying mechanisms. We injected Rh2 into tg2576 Alzheimer's disease model mice and looked for behavioral improvement and senile plaque reduction in brain slices. We measured amyloid precursor protein (APP) metabolism species changes, amyloid beta40 and 42 levels and β, γ secretase activity in primary hippocampal neurons. By livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Harsh amphipathic detergents such as sodium dodecylsulphate can release bound forms from the matrix and disintegrate the large complexes. 39 Ginsenosides are less harsh amphipathic molecules that can destabilize loosely held lipid structures such as liposomes and micelles by both direct interaction with the lipid moieties and chelation of metal ions that normally serve to stabilize the hydrophilic surface of these particles 41,47,56,57 Even in stable cellular domains associated with membrane lipid rafts, ginsenosides are able to dissociate the components within this microdomain leading to a destabilized structure 43,44,58 Their potential for interaction with deposits in Bruch's was therefore investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harsh amphipathic detergents such as sodium dodecylsulphate can release bound forms from the matrix and disintegrate the large complexes. 39 Ginsenosides are less harsh amphipathic molecules that can destabilize loosely held lipid structures such as liposomes and micelles by both direct interaction with the lipid moieties and chelation of metal ions that normally serve to stabilize the hydrophilic surface of these particles 41,47,56,57 Even in stable cellular domains associated with membrane lipid rafts, ginsenosides are able to dissociate the components within this microdomain leading to a destabilized structure 43,44,58 Their potential for interaction with deposits in Bruch's was therefore investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These amphipathic molecules have hydrophilic and hydrophobic domains and can readily partition into lipid structures such as liposomes, micelles, membranes, or lipoidal deposits and assist dispersal. [41][42][43][44] Ginsenosides constitute a group of approximately 30 steroidal amphipathic glycosides found in extracts of the ginseng plant (Panax ginseng CA Meyer). 45 Structurally, they are related to the cholesterol molecule and are divided into two groups, namely protopanaxatriols (e.g., Rg1, Rh2, Re, Rf) and protopanaxdiols (e.g., Rb1, Rb2, Rc, Rd), and individual species are characterized by the type and number of sugar attachments and the attachment site of the hydroxyl group (i.e., C-3, C-6, or C-20; Fig.…”
mentioning
confidence: 99%
“…In recent years, ginseng (an herb commonly used in traditional Chinese medicine) has attracted much attention for its potential in improving cognitive functions (Shi et al, 2010;Liu et al, 2012b;Qiu et al, 2014). Ginsenoside Rh2 (G-Rh2), a saponin isolated from the root of ginseng, was able to attenuate Aβ-induced cytotoxicity in rat brain astrocytes (Shieh et al, 2008).…”
Section: Natural Compounds Targeting P53 Pathway: a Promising Approacmentioning
confidence: 99%
“…Ginsenoside Rh2 (G-Rh2), a saponin isolated from the root of ginseng, was able to attenuate Aβ-induced cytotoxicity in rat brain astrocytes (Shieh et al, 2008). When G-Rh2 was injected into tg2576 AD model mice, it reversed behavioural defects, improved learning and memory performance, and reduced formation of senile plaques at 14 months of age (Qiu et al, 2014). Furthermore, in primary hippocampal neurons, G-Rh2 increased soluble APPα (sAPPα) levels, inhibited APP endocytosis and reduced secretion of Aβ40 and Aβ42 by reducing cholesterol and lipid raft concentrations (Qiu et al, 2014).…”
Section: Natural Compounds Targeting P53 Pathway: a Promising Approacmentioning
confidence: 99%
“…In a pilot Phase 2 clinical study in AD patients, acitretin was shown to significantly increase the sAPPα levels in CSF after a short period of treatment [65]. A longer term study on a larger patient cohort with this drug is planned.Other molecules known to increase ADAM10 expression and/or activity include muscarinic agonists, neuropeptides such as Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP), Protein Kinase C (PKC) activators, phosphatidylinositol 3-kinase, cAMP and calcium [66,67].Ginsenoside Rh2, a ginseng derivative, was found to improve learning and memory in a mouse model of AD [68], and in vitro increased soluble sAPPα. Qiu et al, also used live-cell labeling to show plasma membrane APP levels increased and APP endocytosis decreased, and that this effect was likely due to a reduction in lipid raft levels.…”
mentioning
confidence: 99%